Cross-cultural adaptation of the Greek version of post-COVID-19 Functional Status Scale: assessment of non-hospitalised post-COVID-19 survivors - Maria Tsekoura; Konstantinos Fousekis; Evdokia Billis; Yiannis Dionyssiotis; Elias Tsepis (PAGEPress Publications, 2023)
The objective of the study was to translate and validate into the Greek language and setting the Post-COVID-19 Functional Status (PCFS) scale. Greeks aged ≥18 years who recovered form COVID-19 (≥ 14 days since diagnosis), were invited to participate. This cross-sectional study followed international guidelines regarding the translation process (forward and backward) and the evaluation of the PCFS. Reliability was assessed by test-retest analyses using the intraclass correlation coefficient (ICC) and 95%CI. For the validation, all participants completed the European Quality of Life-5 (EQ-5D-5L), and the Hospital Anxiety and Depression Scale (HADS) questionnaire. 82 adults (49 females, aged 40.2 ± 6.1) participated in the study. The Greek version of the PCFS demonstrated excellent test-retest reliability, with an ICC of 0.9 (95% CI 0.90- 0.95). The Cronbach's alpha value was 0.9, indicating good internal consistency. The PCFS score was strongly correlated with the EQ-5D-5L (r=0.6, p≤0.001) and weakly correlated with the HADS (r=0.41;p≤0.001). The Greek version of the PCFS was successfully adapted into Greek and is recommended to be used across clinical settings and research.